ANALYSIS OF PROJECT MANAGEMENT TRANSMART CARREFOUR IN TEGAL CITY - CENTRAL JAVA - Septi Dwi N.I.S; Saihul Anwar (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
Project implementation is said to be optimal if good project management planning so that it can be done efficiently, qualified, safe, and economical. To produce an optimal project management is required with certain methods adjusted by the project. The purpose of this study is to determine the scheduling of project time to be done by using CPM network method (Critical Path Method) which will result in the length of time of completion of the project and determine the start and end time in each work. The first step is to conduct a field survey, collecting project data such as time schedule, and basic theory. After the data collection is considered enough, then the data is determined again with the method of CPM (Critical Path Method), followed by determining how much the cost to be incurred, and then made barchart and curve S. From the research results obtained, for project implementation can be completed with time work plan 282 days or 47 weeks. But with that time there are some critical work that will affect the duration, so special attention is required on the work. And costs incurred as much as Rp 223,363,901,783.98.Keywords : CPM (Critical Path Method), Duration of Work, Project Cost, Barchart, and Curve S